Sinergi Kader Posyandu Dan Sanitasi Lingkungan Dalam Upaya Penurunan Stunting di Kelurahan Tanjung Mas Kota Semarang - Christine Diah Wahyuninsih (Public Service and Governance Journal, 2025)
This study aims to analyze the synergy between posyandu cadres and environmental sanitation in reducing stunting rates in Tanjung Mas Sub-District, Semarang City. Using a qualitative approach and data collected through observation, interviews, and documentation over the past two years (2023–2024), the research found that community-based interventions through active posyandu cadres, along with improved environmental sanitation, significantly impacted the decline in stunting prevalence in the area. This research adopts the public policy implementation theory of Sabatier & Mazmanian (2022) as well as the cross-sector collaboration theory, and Van Meter and Horns policy implementation theory. Findings indicate that the stunting rate in Tanjung Mas Sub-District decreased from 18.5% in 2022 to 11.2% by the end of 2024. The study recommends strengthening inter-agency coordination, providing ongoing training for posyandu cadres, and improving sanitation infrastructure.